Thermoplastic Elastomer (TPE) Composites with Modified Fibers and Hemp Shives – an Ecological Approach to Modern Polymer Materials - Karol Tutek; Anna Kosmalska-Olańska; Anna Masek (Journal of Natural Fibers)
This work investigates the potential application of sustainable materials based on thermoplastic elastomer (TPE) polymers reinforced with cellulose derived from environmentally friendly hemp. The increasing cultivation of hemp and the resulting waste, such as cannabinoid extraction residues, prompted an exploration of hemp-based materials for various applications. Ethylene-norbornene copolymer, widely used in packaging, was chosen as polymer matrix. Various hemp derivatives, including fibers and shives, were incorporated to enhance the bio-based content of the material. The study focused on the effect of two commonly used surface modifiers for cellulosic materials: maleic anhydride and N-2-aminoethyl-3-aminopropyltrimethoxysilane. Both modifiers were used to enhance the interfacial adhesion between the polymer matrix and the filler, while inducing a partial hydrophobization of the bioadditive. This research presents a novel approach using hemp shives as biofillers for TPE-based polymeric materials, facilitated by their facile mechanochemical modification. The modified fillers and resulting composites were subjected to a comprehensive series of mechanical, thermal, spectroscopic and microscopic analyses, complemented by measurements of surface free energy changes. The resulting materials demonstrated a significant increase in the initial thermal decomposition temperature and enhanced dispersion of the modified biofiller withinthe polymer matrix. These findings indicate their potential for use in flexible and environmentally sustainable packaging materials.